Sources of the Possibility of the Contemporary turn towards Religion - Torzewski, Antoni (Humaniora. Czasopismo Internetowe, 2020)
The return of religion in the philosophical reflection can be observed in the contemporary world. Thinkers like Richard Rorty, Gianni Vattimo or Charles Taylor can substantially exemplify that phenomenon. In this paper, we would like to focus on some of the aspects of modern and contemporary philosophy of religion and also on the sources that made it even possible. That is why at first we point out three critiques of religion present mostly in the XVIII-th and XIX-th century. Then we will inquire about the two main ways of understanding religion in the contemporary philosophy and about it’s source.